A horta orgânica como ferramenta no ensino de Botânica - Bini, Emilly Guimarães (2019)
This paper aims to present a teaching proposal of Botany for High School, through activities carried out with an organic garden, sourching to contextualize it to the reality of students. Given that the content of Botany is, in general, little addressed in the classroom by professionals of basic education, because they don´t master the subject, and when they do they treat it superficially, promoting mechanical learning aiming only at Obtaining grades during the evaluation, this research sought to approach the theme from the perspective of Meaningful Learning Theory, with a contextualized and practical alternative, through the elaboration of a Didactic Sequence. The intention is to offer the arguments and references for the construction and deepening of the contents of morphology, anatomy and plant physiology, through plants cultivated in an organic garden, besides providing a reflection on healthy eating. The methodological work is characterized by qualitative research, with emphasis on participatory research, through the application of a didact Sequence in a state school in the city of Várzea Grande – MT. Data analysis was performed qualitatively in three moments (survey of previous knowledge; activities developed in the Didactic Sequence; and, finally, concept maps) and showed that the students were able to express, through concept map, the contents that were acquiring meaning in their cognitive structure. Thus, it is believed that it was possible to show that the elaboration of planned and contextualized activities, aiming to ensure a better approach to the Botany content, can promote the construction of meaningful learning with sucessful.